Analisis Produksi Tanaman Karet di Desa Terbangiang Kecamatan Bandar Petalangan Kabupaten Pelalawan - Rini Sisuanti; Mardiana '; Nobel Aqualdo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted in the Village of Terbangiang Bandar Petalangan Pelalawan. The purpose of this study was to determine the factors thatinfluence the production of rubber, how the condition of scale and efficient use of capital and labor in the rubber plant in the Village of Terbangiang Bandar Petalangan Pelalawan. In this study, the population is around the rubber farmers in the Village of Terbangiang Bandar Petalangan Pelalawan in 2013, as many as 221 families. The sampling technique used is random sampling, ie random sampling technique. Where the number of samples taken 69 samples of the population. Methods of data analysis used in this study was descriptive quantitative, where all the values of the variables obtained in the natural logarithm transformed and continued to analyze the data and simultaneous partial. Simultaneous testing (F test) showed that capital and labor jointly significantly affect the production of rubber trees in the Village of Terbangiang Bandar Petalangan Pelalawan. With the calculated F value of 19,508 and the value of F table at 3.980. Based on calculations known value of 0.512 or 51.20% R2 sebesar factors affecting the production of rubber plants are capital and labor. Rubber plant scale production effort to describe Decreasing Scale. The use of capital and labor in the production of rubber plants are not efficient.Keywords: Rubber Plant Production, Capital, Labor